Effect of Optic Flow on Postural Control in Children and Adults with Autism Spectrum Disorder. (21st November 2018) - Lim, Yi Huey; Lee, Hoe C.; Falkmer, Torbjörn; Allison, Garry T.; Tan, Tele; Lee, Wee Lih; Morris, Susan L.
Highlights: Children and adults with autism spectrum disorder (ASD) may not display poor postural control all the time. Only adults with ASD appeared more sensitive to forward-moving optic flow presented in the peripheral visual field. Adults with ASD may have difficulty prioritizing visual information across visual fields. Abstract: Individuals with autism spectrum disorder (ASD) have been associated with sensorimotor difficulties, commonly presented by poor postural control. Postural control is necessary for all motor behaviors. However, findings concerning the effect of visual motion on postural control and the age progression of postural control in individuals with ASD are inconsistent. The aims of the present study were to examine postural responses to optic flow in children and adults with and without ASD, postural responses to optic flow in the central and peripheral visual fields, and the changes in postural responses between the child and adult groups. Thirty-three children (8–12 years old) and 33 adults (18–50 years old) with and without ASD were assessed on quiet standing for 60 seconds under conditions of varying optic flow illusions, consisting of different combinations of optic flow directions and visual field display. The results showed that postural responses to most optic flow conditions were comparable between children with and without ASD and between adults with and without ASD. However, adults with ASD appeared more responsive to forward-moving optic flow in the peripheral visual field compared with typically developed adults. The findings suggest that children and adults with ASD may not display maladaptive postural responses all the time. In addition, adults in the ASD group may have difficulties prioritizing visual information in the central visual field over visual information in the peripheral visual field when in unfamiliar environments, which may have implications in understanding their motor behaviors in new surroundings.